Nutritional-associated changes in lipid metabolism affecting the pathogenicity of Cryptococcus neoformans - Bhana, Zoe Tyler (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2022.